What price the court of St. James? Political influences on ambassadorial postings of the United States of America. Issue 3 (17th November 2016) - Fedderke, Johannes; Jett, Dennis
Abstract: This paper explores the appointment of career diplomats and political appointees to ambassadorial positions. We present models of the strategic interaction of political donors and presidential candidates, which predicts that donations will match the quality of diplomatic posting granted by the candidate. We test this prediction and confirm it for four presidential terms representing two presidents and 764 diplomatic postings over the 2000 to 2013 period. This allows for the generation of a price list associated with a range of desirable diplomatic posts. This paper provides evidence in support of the proposition that ambassadorships, in locations that are deemed desirable such as Western Europe, are awarded as a form of patronage in return for campaign contributions.